1999
DOI: 10.1046/j.1463-5224.1999.00076.x
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic materials in veterinary ophthalmology

Abstract: Viscoelastic materials have applications in both human and veterinary ophthalmology and orthopedics and for humans in otorhinolaryngology, urinary incontinence, cosmetic surgery and cosmetics. In ophthalmology, viscoelasties are most commonly used in facilitating cataract and other anterior segment surgeries, but also have applications in posterior segment surgery and in the topical management of keratoconjunctivitis sicca. Viscoelastics are routinely used during anterior segment surgery in filling and maintai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 22 publications
0
31
0
Order By: Relevance
“…In a study comparing the removal of visco‐elastic materials after experimental cataract surgery, Assia showed that sodium hyaluronate is the most easily, rapidly and completely removed 14 . However, its high cohesiveness also increases the tendency to plug the trabecular meshwork, resulting in an acute increase in postoperative IOP 16 . The various properties of visco‐elastic agents used in cataract surgery may explain the different results concerning the incidence of acute POH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study comparing the removal of visco‐elastic materials after experimental cataract surgery, Assia showed that sodium hyaluronate is the most easily, rapidly and completely removed 14 . However, its high cohesiveness also increases the tendency to plug the trabecular meshwork, resulting in an acute increase in postoperative IOP 16 . The various properties of visco‐elastic agents used in cataract surgery may explain the different results concerning the incidence of acute POH.…”
Section: Discussionmentioning
confidence: 99%
“…Sodium hyaluronate appears to be most easily, rapidly and completely removed in comparison with chondroitin sulfate‐sodium hyaluronate, hydroxypropylmethylcellulose and polyacrylamide 14 . However, as with other visco‐elastic materials, the risk of postoperative ocular hypertension (POH) remains if it is not well aspirated at the end of surgery 16 …”
Section: Introductionmentioning
confidence: 99%
“…The use of a combination of 3% sodium hyluronate-4% chondroitin sulfate (dispersive) and 1% sodium hyaluronate (cohesive) has been recommended (Arshinoff, 1999;Wilkie and Willis, 1999). Pigatto (2004) studied corneal endothelial repercussions in dogs submitted to phacoemulsification and EE using the same combination of viscoelastic agents in a soft-shell technique.…”
Section: Discussionmentioning
confidence: 99%
“…It was also determined that preoperative IOP did not significantly correlate with POH [17,18 ]. The prevalence of POH may be reduced by complete removal of the viscoelastic material [49,50]. Other methods to control POH include intracameral injection of carbachol or tPA or preoperative use of carbonic anhydrase inhibitors.…”
Section: Postoperativementioning
confidence: 99%